MyD88 Dependent Signaling Contributes to Protective Host Defense against Burkholderia pseudomallei - Wiersinga, W. Joost (Public Library of Science, 2008)

(untitled)
BACKGROUND: Toll-like receptors (TLRs) have a central role in the recognition of pathogens and the initiation of the innate immune response. Myeloid differentiation primary-response gene 88 (MyD88) and TIR-domain-containing adaptor protein inducing IFNβ (TRIF) are regarded as the key signaling adaptor proteins for TLRs. Melioidosis, which is endemic in SE-Asia, is a severe infection caused by the gram-negative bacterium Burkholderia pseudomallei. We here aimed to characterize the role of MyD88 and TRIF in host defense against melioidosis. METHODOLOGY AND PRINCIPAL FINDINGS: First, we found that MyD88, but not TRIF, deficient whole blood leukocytes released less TNFα upon stimulation with B. pseudomallei compared to wild-type (WT) cells. Thereafter we inoculated MyD88 knock-out (KO), TRIF mutant and WT mice intranasally with B. pseudomallei and found that MyD88 KO, but not TRIF mutant mice demonstrated a strongly accelerated lethality, which was accompanied by significantly increased bacterial loads in lungs, liver and blood, and grossly enhanced liver damage compared to WT mice. The decreased bacterial clearance capacity of MyD88 KO mice was accompanied by a markedly reduced early pulmonary neutrophil recruitment and a diminished activation of neutrophils after infection with B. pseudomallei. MyD88 KO leukocytes displayed an unaltered capacity to phagocytose and kill B. pseudomallei in vitro. CONCLUSIONS: MyD88 dependent signaling, but not TRIF dependent signaling, contributes to a protective host response against B. pseudomallei at least in part by causing early neutrophil recruitment towards the primary site of infection.